Phenotypic effects of jointless gene in tomato - El Sayed, Mohamed H. K., author; Foskett, Richard L., advisor; Chapman, Harold W., committee member; Parke, Robert V., committee member (Colorado State University. Libraries, 1962)
A study of the pleiotropic effects of the jointless gene in tomato (j1) was conducted in both the greenhouse and the field. This gene was found to mask the determinate character, controlled by a single recessive gene (sp.). This effect was found by crossing the phenotypically indeterminate and jointless variety Dwarf Champion with known indeterminate and determinate jointed varieties. The F1 of the cross with an indeterminate variety was indeterminate, but there were determinate segregates in the F2 progeny. Furthermore, the F1 of the cross with a known determinate and no indeterminate-jointed plants were observed in the F2 generation. All jointless plants in this study were phenotypically indeterminate. There were fewer flowers per inflorescence on jointless plants than on jointed plants in all progenies and treatments in the study. It was also noted that the modul number of all jointless populations was three. This number remained constant in F2 populations regardless of jointed parent. It was also not increased by removing leaves after the fourth node, a treatment which increased the number of flowers in jointed inflorescences. Although the jointless character decreased number of flowers per inflorescence, the percentage of flowers setting fruits was higher among jointless plants than among jointed. This resulted in almost as many fruits per inflorescence among jointless plants as among jointed. Number of days until the opening of first flower and number of nodes before the first inflorescence were in all cases greater among jointless plants than among jointed. Eight inflorescences were observed from each plant in the field study. In this study all jointless plants had some leafy inflorescences and all the observed inflorescences were leafy in 33 percent of the jointless plants. On the other hand, 70 percent of the jointed plants had no leafy inflorescences and no jointed plants were found with more than four of the eight inflorescences leafy.
Covers not scanned.
Keywords: Tomatoes